Colloidal Superstructures Programmed into Magnetic Janus Particles. (12th December 2014) - Yan, Jing; Bae, Sung Chul; Granick, Steve
<x xml:space="preserve">Abstract</x> By engineering thin magnetic films onto homogeneous colloidal particles, various crystalline lattices are induced from simple magnetic Janus spheres. In situ formation of dicolloids amplifies the diversity of achievable dynamic structures. The competition between shape anisotropy and dipole orientation generates mesoscopic isomerism. This opens design space for anisotropic building blocks for smart colloidal materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>